Physical Evidence - Arifi, Besim (European Journal of Multidisciplinary Studies, 2016)
One of the first actions that the investigation group after arriving in the crime scene or after receiving that call for a crime that has happening is ensuring that evidence and material prove found or can be found at that mentioned location. Documentation of the prove and evidence are important for the entire investigative process during all phases of criminal proceedings in general. Search, finding, photography, picking, packing, examination and presentation in court are the main steps regarding evidence, whether physical or real, whether they witnessed or en the form of statements. Given that evidence is calculated everything in crime scene, until argued the opposite, then for their management and required a cautious professional approach. This care for proper performance of the road that makes the testimony or evidence material ensures and guarantees the preservation of the chain of testimony. So this whole chain filed past the alignment of finding up to presentation trial.